ANALYSIS OF THE EFFECT OF TRAINING ON THE PERFORMANCE OF GENERATION Z EMPLOYEES IN THE VUCA ERA (VOLATILITY, UNCERTAINTY, COMPLEXITY, AND AMBIGUITY) - Ramon Syahrial (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
This study aims to examine and analyze the Effect of Training on the Performance of Generation Z Employees in the Vuca Era (Volatility, Uncertainty, Complexity, and Ambiguity). The method used in this study is a quantitative associative approach. This research was conducted at PT Pilar Pualam Surabaya. The sample in this study amounted to 68 people with a sampling technique that is purposive sampling. Data collection techniques through observation, questionnaires (questionnaire), interviews, and literature. The questionnaire used has been tested for validity and reliability. The data analysis technique used is a simple regression analysis technique with the help of statistical software SPSS version 24. The results of this study show that training has an effect on the performance of Generation Z employees in the Vuca Era (Volatility, Uncertainty, Complexity, and Ambiguity). The results of this study mean that to improve the performance of Generation Z employees in the Vuca Era, companies need to conduct training that can support employees' professionalism.